Pendampingan Pengenalan Program Sem-Pls Pada Fakultas Ekonomi Universitas Merdeka Surabaya - Sri Yunan Budiarsi (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
This activity is designed to provide training and assistance in carrying out the Partial Least Squares - PLS 03 program. In addition to providing assistance in reading and analyzing the results / outputs of the PLS 03 program, as well as reporting. There have not been many studies in the Faculty of Economics, University of Merdeka Surabaya that use PLS version 03, because it is relatively new and the program price is quite expensive. In this case, for more than 100 data you must use the PLS 03 professional, but for data up to 100 you can use the PLS 03 Student Version. On the other hand, there are more and more demands for its use, in accordance with the development of research in the field of business / management. For this reason, the introduction and training of PLS is needed in order to have the most suitable alternative SEM method in order to obtain better research results. This PLS 03 workshop is intended for teaching staff and students who program thesis at the Faculty of Economics, Universitas Merdeka who later want to use the PLS 03 SEM method in data processing.